The utility of written corrective feedback in L2 learning: analysis of an experience with Erasmus incoming students - Silvia Gasparini (Firenze University Press, 2019)
Leaving aside the problem of positive reinforcement, the only problem of the choice and use of corrective feedback is a subject of critical importance for L2 (second language) learning in a constructivist/interactionist perspective. The problem interfaces with the increasingly widespread use of information technology applied to language learning (Intelligent Tutoring System and Computer Assisted Language Learning technologies). Against the background of this complex scenario, the article aims to evaluate the effectiveness of peer-delivered corrective feedback in an intervention carried out with Erasmus students who learn the Italian language. Three different ways of providing written feedback are compared: (i) the direct substitution mode; (ii) the indirect feedback mode using metalinguistic codes; (iii) the indirect feedback mode using codes plus concrete examples. In line with the literature, the experiment results demonstrate that the forms of indirect feedback (conditions ii) and iii)) guarantee better long-term learning than direct feedback (condition i)). However, the advantage of integrating examples into indirect feedback is not clear.   L'utilità del feedback correttivo scritto nell'apprendimento di L2: analisi di un'esperienza con studenti Erasmus. Lasciando da parte il problema del rinforzo positivo, il solo problema della scelta e dell'uso del feedback correttivo è un argomento di fondamentale importanza per l'apprendimento L2 in una prospettiva costruttivistica/interazionista. Il problema si interfaccia con l'uso sempre più diffuso della tecnologia informatica applicata all'apprendimento delle lingue (tecnologie Intelligent Tutoring System e Computer Assisted Language Learning). Sullo sfondo di questo scenario complesso, l'articolo mira a valutare l'efficacia del feedback correttivo in un intervento condotto con studenti Erasmus che apprendono la lingua italiana. Vengono confrontati tre diversi tipi di peer feedback applicati a una composizione scritta: (i) feedback diretto; (ii) feedback indiretto, utilizzando informazioni metalinguistiche; (iii) feedback indiretto, utilizzando informazioni metalinguistiche più esempi concreti. In linea con la letteratura, i risultati dimostrano che le forme di feedback indiretto (condizioni ii) e iii)) offrono un migliore apprendimento a lungo termine rispetto al feedback diretto condizione i)). Non risulta tuttavia chiaro il vantaggio apportato dall'integrazione nel feedback indiretto di esempi.